ULOGA VEŠTAČKE INTELIGENCIJE U PRODAJI I MARKETINGU - Pashtranjaku, Klea; Mansi, Egla; Koroglu, Osman (International Journal of Economic Practice and Policy, 2025)
This paper presents a systematic literature review on the role of artificial intelligence (AI) in sales and marketing, using the PRISMA methodology. It explores the influence of AI on sales performance, customer relationship management, marketing effectiveness, and decision-making processes. The study provides a holistic view of how AI contributes to success in these fields, elucidating the connection between AI and professional success. This research offers opportunities to enhance recruitment, training, and development strategies, contributing to a deeper understanding of AI’s role in the competitive world of sales and marketing. By synthesizing existing knowledge, it paves the way for informed decision-making and strategic development in the industry.
Keywords: artificial intelligence; sales; marketing; PRISMA; customer relationship management